2014
DOI: 10.1111/eos.12114
|View full text |Cite
|
Sign up to set email alerts
|

5,10‐Methylenetetrahydrofolate reductase single nucleotide polymorphisms and gene–environment interaction analysis in non‐syndromic cleft lip/palate

Abstract: Non-syndromic cleft lip/palate (NSCL/P) is a common congenital defect in Mexico. Periconceptional intake of folic acid (FA) may reduce the risk of this malformation. Although the 5,10-methylenetetrahydrofolate reductase (MTHFR) enzyme participates in folate metabolism, several studies failed to find any association between NSCL/P and the MTHFR C677T and A1298C polymorphisms. However, interactions among NSCL/P, MTHFR gene polymorphisms, and FA intake have not been explored in Mexican populations. This case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…This result reflects the complexity of the model where two copies of the risk allele could be necessary to increase the phenotype susceptibility. Both positive and negative results of association have been previously described in other Latin American case–control populations (Gaspar et al , ; Sözen et al , ; Estandia‐Ortega et al , ; Bezerra et al , ). Multiethnic meta‐analyses for genotypes (TT vs CC) present highly similar results to ours showing overall ORs of 1.21 (95% CI 0.97–1.53; Pan et al , ) and 1.22 (95% CI 0.97–1.55; Luo et al , ).…”
Section: Discussionsupporting
confidence: 53%
“…This result reflects the complexity of the model where two copies of the risk allele could be necessary to increase the phenotype susceptibility. Both positive and negative results of association have been previously described in other Latin American case–control populations (Gaspar et al , ; Sözen et al , ; Estandia‐Ortega et al , ; Bezerra et al , ). Multiethnic meta‐analyses for genotypes (TT vs CC) present highly similar results to ours showing overall ORs of 1.21 (95% CI 0.97–1.53; Pan et al , ) and 1.22 (95% CI 0.97–1.55; Luo et al , ).…”
Section: Discussionsupporting
confidence: 53%
“…Out of 31 studies included in the present meta-analysis, six studies 27,34,39,44,45,52 , five studies 34,39,44,46,52 , and four studies 34,39,46,52 reported significantly increased risk of T allele, TT genotype, and CT genotype in NSCL/P patients compared with controls, respectively. Also, five studies 36,47,49,55,57 , two studies 47,57 , and four studies 28,36,47,57 reported a significantly decreased risk of T allele, TT genotype and CT genotype in NSCL/P patients compared with controls, respectively. In addition, TT + CT genotype was reported to have a significantly increased risk in five studies 34,39,44,46,52 and significantly decreased risk in four studies 36,47,55,57 in NSCL/P patients compared with controls.…”
Section: Discussionmentioning
confidence: 98%
“…Also, five studies 36,47,49,55,57 , two studies 47,57 , and four studies 28,36,47,57 reported a significantly decreased risk of T allele, TT genotype and CT genotype in NSCL/P patients compared with controls, respectively. In addition, TT + CT genotype was reported to have a significantly increased risk in five studies 34,39,44,46,52 and significantly decreased risk in four studies 36,47,55,57 in NSCL/P patients compared with controls. Based on the recessive model, three studies 39,46,54 reported significantly increased risk of TT genotype and one study 57 reported its significantly decreased risk in NSCL/P patients compared with controls.…”
Section: Discussionmentioning
confidence: 98%
“…The development of craniofacial structures is the product of social environmental, and nutritional factors such as tobacco smoke, alcohol consumption, and maternal folic acid deficiency due to exposure to folic acid antagonists – such as anticonvulsants 26 – appear to play a role in the development of OFC during pregnancy 8 . Folic acid is a water soluble B-vitamin that plays a crucial role in embryonic development because it is essential for DNA stability maintenance, being involved in DNA synthesis, repair, and methylation 4 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic cycle of folate is complex, with multiple genes participating in the transformation of folate into various compounds 8 . One of these genes is dihydrofolate reductase (DHFR), known as a strong candidate for a teratogenic locus which synthesizes the DHFR enzyme.…”
Section: Introductionmentioning
confidence: 99%